A report of a species of the genus Acanthobothrium coronatum (Eucestoda: Onchobothridae) from Rhynchobatus djeddensis from Bombay (M.S.), West coast of India, India - Khamkar, D D (Journal of Experimental Sciences, 2012)
This paper deals with the redescription of a cestode from marine fishes in Maharashtra i.e. Acanthobothrium coronatum (Rudolphi, 1819) [1] Van Beneden, 1849 [2].